Potential effects of induced focal ischemia in the motor cortex of rats undergoing experimental periodontitis - Victória dos Santos Chemelo; Marco Aurelio M. Freire; Leonardo Oliveira Bittencourt; Deborah Ribeiro Frazão; Deiweson Souza-Monteiro; Sabrina C. Cartagenes; Walace Gomes-Leal; Cristiane do Socorro Ferraz Maia; Gabriel S. Rocha; Daniel Falcao; Rafael Rodrigues Lima (Heliyon)
Stroke is a severe medical condition resulting from an interruption in the blood supply to the brain, ultimately compromising tissue homeostasis. Currently, stroke stands as the second leading cause of death worldwide and the third leading cause when considering both mortality and disability together. Periodontitis is characterized by persistent inflammation in hard and soft tissues which support the teeth, primarily caused by bacterial biofilms, and is one of the most common causes of tooth loss in adults and can contribute to a systemic inflammatory burden. In the light of this, the present study investigated the effects of inducing focal ischemia in the motor cortex in rats undergoing experimental periodontitis. Adult Wistar rats were divided into four groups (control, ischemia, periodontitis, and periodontitis + ischemia) and were evaluated for motor performance, basic histology, and the volume and microarchitecture of alveolar bone. The results showed that the comorbidity between ischemia and periodontitis aggravates the spontaneous locomotion of rats, although the motor performance of adult rats had not been altered. Nonetheless, they revealed significant tissue impairment in the motor cortex. Additionally, there was a meaningful alteration in both the volume and microarchitecture of alveolar bone in this group. Our results indicate that the model of comorbidity between ligature-induced experimental periodontitis and focal ischemia was capable of inducing greater neurological impairment and alveolar bone loss in rats, attributable to diminished bone quality, when compared to each condition individually.